Order in Product Customization Decisions: Evidence from Field Experiments - Levav, Jonathan; Heitmann, Mark; Herrmann, Andreas; Iyengar, Sheena S. (Journal of Political Economy, 2010)
Differentiated product models are predicated on the belief that a product’s utility can be derived from the summation of utilities for its individual attributes. In one framed field experiment and two natural field experiments, we test this assumption by experimentally manipulating the order of attribute presentation in the product customization process of custom‐made suits and automobiles. We find that order affects the design of a suit that people configure and the design and price of a car that people purchase by influencing the likelihood that they will accept the default option suggested by the firm.